Formaldehyde exposure and its effects during pregnancy - Haffner, Matthew J. (2019)
Formalin is commonly used in fixation of cadaveric specimens. Exposure to formaldehyde, a component of formalin and a known carcinogen, during gross anatomy laboratory dissection is a continuing concern for pregnant students and instructors. Since there is little literature on this specific topic, the current review was compiled in the hope of offering recommendations to pregnant students and instructors who are engaged in human anatomical dissection where formalin is used. Relevant articles were obtained through searches of PubMed and Google Scholar for the terms “formaldehyde,” “pregnant,” “formalin,” and “exposure.” A literature search was conducted for chemical information and articles about exposure as issued by government regulatory agencies and chemical companies that produce formaldehyde. This led to the compilation of 29 articles each of which included references to previous, relevant, human research. The reviewed literature contains data strongly suggesting that pregnancy can be affected by formaldehyde exposure. Therefore, on the basis our analysis, female students who might be pregnant should avoid formaldehyde exposure, including that in a gross anatomy laboratory. Instructors should find other means of ensuring anatomical competence for these students.